125k views
0 votes
Solve f - 6 = 3f + 1

2 Answers

4 votes
Simplifying f + -6 = 3f + 1 Reorder the terms: -6 + f = 3f + 1 Reorder the terms: -6 + f = 1 + 3f Solving -6 + f = 1 + 3f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-3f' to each side of the equation. -6 + f + -3f = 1 + 3f + -3f Combine like terms: f + -3f = -2f -6 + -2f = 1 + 3f + -3f Combine like terms: 3f + -3f = 0 -6 + -2f = 1 + 0 -6 + -2f = 1 Add '6' to each side of the equation. -6 + 6 + -2f = 1 + 6 Combine like terms: -6 + 6 = 0 0 + -2f = 1 + 6 -2f = 1 + 6 Combine like terms: 1 + 6 = 7 -2f = 7 Divide each side by '-2'. f = -3.5 Simplifying f = -3.5

User Andrew Bennet
by
6.2k points
1 vote
f-6=3f+1
-6-1=3f-f
-7=2f
-7รท2=f
-3.5=f
User RobV
by
6.0k points